2019
DOI: 10.3390/ijerph16071141
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Understanding of Infant Feeding Guidelines and Their Associated Practices: A Qualitative Analysis

Abstract: There is limited evidence to describe Australian mothers’ understanding of the Australian Infant Feeding Guidelines (AIFG). A qualitative inductive methodological approach was used in this study to explore experiences with the introduction of solid food. Seven focus groups with 42 mothers of children aged 4–18 months were conducted in disadvantaged areas in Perth, Australia. The mean age of infants was 9.6 months and mean age of introduction of solid food was 4.3 months (range 1.2 to 7.5 months). Almost half o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 50 publications
5
53
0
1
Order By: Relevance
“…CFHNs also reported lack of appropriate resources such as resources not tailored to cultural and religious groups [56,71], and lack of services or resources in community languages or simple English CFHNs in this study reported high confidence in providing advice about introducing solid foods and healthy eating behaviours, although some were less confident in growth monitoring and identifying risk of overweight and obesity. However, previous research has shown that Australian parents require more education on evidence-based introduction of solids, to increase their understanding on infants' readiness and to counter inaccurate guidance from family members or commercial baby food packaging [74]. Another study on Australian parents with children aged 2-5 years reported that CFHNs 'brushed over' their child's weight issues and offered limited advice [75].…”
Section: Discussionmentioning
confidence: 99%
“…CFHNs also reported lack of appropriate resources such as resources not tailored to cultural and religious groups [56,71], and lack of services or resources in community languages or simple English CFHNs in this study reported high confidence in providing advice about introducing solid foods and healthy eating behaviours, although some were less confident in growth monitoring and identifying risk of overweight and obesity. However, previous research has shown that Australian parents require more education on evidence-based introduction of solids, to increase their understanding on infants' readiness and to counter inaccurate guidance from family members or commercial baby food packaging [74]. Another study on Australian parents with children aged 2-5 years reported that CFHNs 'brushed over' their child's weight issues and offered limited advice [75].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it can be inferred that the high level of self-efficacy was essential for the practice of breastfeeding initiated and carried out in the maternity ward; however, when returning to their homes, it is observed that breastfeeding did not depend only on the mastery of management techniques and on the desire shown in the hospital setting. Internal personal aspects and factors of each woman's life context are also directly involved in the preparation and delivery of the child's food, insofar as she interprets and adjusts the official recommendations according to her reality (20) , which may have influenced www.eerp.usp.br/rlae In the analysis of associations between the sociodemographic variables and EBF duration at 30, 60, and 180 days after delivery, the "religion" variable had an influence on maintaining this practice at 30 and 60 days after delivery. Considering that individual and population health determinants bring together customs, beliefs, and values, and that this includes religious culture, the choice of women to breastfeed may or may not be influenced by religion or by adhering to traditional or modern values of a given population (21) .…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies in this review addressing introduction of solid or semi-solid foods, "beliefs, values, and perceived norms" were a central influence on complementary feeding practices [43,44,49,51,55,59,85,88,89,[91][92][93][94][95][96][97][98][99], which brought challenges to immigrant mothers of children who were culturally separated [100,101]. Parents perceived that "everyone gives you advice" [102], and complementary feeding was viewed as a natural progression with the goal of enjoyment of food and development of an expansive palate [95]. Considerations of infants' own preferences [93], as well as responsiveness to family needs and wants [92] were determinants of food choices.…”
Section: Infant Feeding Behaviors Are Influenced By the Socio-culturamentioning
confidence: 99%
“…"Cost, location, and access to fresh and traditional foods" [85,93,96] was a priority. Some parents reported dissatisfaction with the "one size fits most" approach of infant feeding guidance as "every child is different" [97,102] and reported relying on their own instincts, or cultural familiarity when deciding what and how to feed their infant.…”
Section: Infant Feeding Behaviors Are Influenced By the Socio-culturamentioning
confidence: 99%